On the definition of threshold voltage for tunnel FETs. (July 2017) - Mori, Yoshiaki; Sato, Shingo; Omura, Yasuhisa; Chattopadhyay, Avik; Mallik, Abhijit
Abstract: This paper proposes how to experimentally define the threshold voltage for various TFETs based on the theoretical point of view. We propose that the gate voltage defined corresponding to the peak of normalized transconductance is effectively the threshold voltage of TFETs. We also demonstrate that this definition is valid for different structures of TFET. In addition, we address the short-channel effect with such definition of threshold voltage for lateral TFET. It is shown that the short-channel effect significantly increased the off-current and the threshold voltage due to the extension of the drain potential and degradation of gate-field integrity in TFETs. Highlights: Threshold voltage definition for TFETs. Short-channel devices. Lateral TFETs and vertical TFETs.